Fostering Inclusion in Italy: Analyzing the 2022 Educational Guidance Reforms for Students with Disabilities - Valentina Della Volpe (European Scientific Journal, ESJ, 2025)
The educational guidance and inclusion practices in Italian schools have undergone significant evolution over the last few years. Recent legislative updates emphasize equity, inclusion, and personalized educational paths, acknowledging the diverse backgrounds, languages, and abilities of students. The 2022 guidelines for school guidance, introduced within the framework of the National Recovery and Resilience Plan (NRRP), further underline the importance of creating an inclusive educational environment. This article explores the most recent regulations from 2020 alongside the latest Eurydice reports to analyze their implications for inclusive education, the role of pedagogical frameworks, and strategies to advance equity and accessibility in schools. By integrating legislative analysis, pedagogical frameworks, and comparative European perspectives, the study identifies challenges and proposes strategies for improving accessibility, teacher training, and systemic collaboration to ensure the realization of inclusive education for every student.